Non-native PGPB consortium consisting of Pseudomonas sp. G31 and Azotobacter sp. PBC2 promoted winter wheat growth and slightly altered the native bacterial community - J. Dobrzyński; I. Kulkova; Z. Jakubowska; B. Wróbel (Scientific Reports)
Abstract Plant growth-promoting bacteria (PGPB) are considered an effective eco-friendly biostimulator. However, relatively few studies have examined how PGPB affect the native bacterial community of major crops. Thus, this study investigates the impact of a PGPB consortium, comprising Pseudomonas sp. G31 and Azotobacter sp. PBC2 (P1A), on the soil bacterial community of wheat under field conditions. As a result of PGPB application, we observed a significant increase in seed yield, as well as in nitrate content (1st and 3rd time points) and available phosphorus (2nd time point) in the rhizosphere compared to control. For the metataxonomic study, Next-Generation Sequencing was performed using the Illumina NovaSeq 6000 system. The consortium used did not have a significant impact on the diversity of native soil bacteria and slightly affected the taxonomic composition of bacteria with no significant changes in bacterial dominants at the phylum and genus level. Nevertheless, 3 weeks after application, P1A increased the relative abundance of Nitrospira which could have influenced the increase in nitrates in the rhizosphere, and also decreased Bdellovibrio. The results indicate that the P1A consortium, due to its ability to promote plant growth without detrimental alternations in the bacterial community of the soil, may be a potential candidate for commercialization.